Sosialisasi Upaya Pengenalan dan Pengembangan Usaha Mikro Kecil Menengah (UMKM) Desa Sukajaya - Ranny Meilisa; Lia Ainurrahmah; Muhamad Arif; Kholilullah Kholilullah (Gapenas Publisher, 2022)
Efforts to introduce and develop Micro, Small and Medium Enterprises (MSMEs) have an important role and strategy in national economic development. In addition to playing a role in economic growth, it also plays a role in the absorption of labor on a large scale. Sukajaya village has a very large area of ??agricultural land and ponds. So that the community can take advantage of the results of their village to raise the village MSMEs. This Community Service (UMKM) activity is carried out with socialization activities and implementation methods such as observation and interviews, lectures and discussions, as well as demonstrations and practices. Based on the phenomenon of existing thinking, efforts are needed to increase public interest in MSMEs and provide motivation to the community to continue running a business or take advantage of existing opportunities to open a business. This socialization also explains the importance of marketing on social media and also utilizing technology for business development